Effects of varying numbers of Likert scale points on factor structure of the Rosenberg Self‐Esteem Scale. Issue 3 (16th April 2018) - Xu, Meng Lin; Leung, Shing On
Abstract : Likert‐type rating scales are among the most widely used tools in psychological research. Different numbers of response categories would likely affect response style, data distribution, reliability, and construct validity. There is a lack of research in factor structure invariance under Likert scales with different numbers of categories. The purpose of this study is to examine the effects of varying numbers of Likert points (4–11) on scale properties such as factor structure, external validity, and latent means based on the Rosenberg Self‐Esteem Scale (M. Rosenberg, 1989 ). The sample consists of 1, 807 students from secondary schools in Macau. Confirmatory factor analysis shows that the correlated two‐factor model is the most appropriate one; longitudinal invariance analysis reveals that measurement invariance across Likert scales was satisfied at the scalar level. In addition, latent mean scores on the two factors as well as observed means on the subscales are comparable across Likert scales. Moreover, the measurement model across Likert scales exhibit similar external validity. Although psychometric properties are mostly similar among a different number of points, the 4‐point Likert scale is not recommended for its higher skewness and lower loadings; the 11‐point Likert scale from 0 to 10 is slightly preferred for its higher loadings and composite reliability.